(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In the sawmill industry in Latvia the roundwood represents about 70 % of the total production cost. The quantity measurements of the round wood are required throughout the logic chain of wood from forest to the sawmills but inspite of a large proportion of the total cost the term “true volume” of roundwood is equally actual for supplies and processors of wood. The roundwood volume results differ measured the same load by measuring the diameters of log in short intervals using harvester measurement systems and in sawmills by measuring the diameters of log in short intervals using electronic 3D systems or measured manually using the most accurate method according to the requirements of standard LVS 82:2003 by measuring top and butt diameter. This means that it is a great interest in industry to develop the measurement methods and systems to have a lower cost and more efficient algorithm to determine the wood volume.The purpose of this study is to compare the wood volume calculation results made by the most accurate manual and automatic measurement methods and give the recommendations for minimizing difference between them.The research is a continuation to the work done in the project „Harmonisation of piece-by-piece measurement methods of roundwood approved by Standard LVS 82:2003 „Apaļo kokmateriālu uzmērīšana” (Miklasevics, Z., 2013).